Achieving the composite endpoint of glycated haemoglobin <7.0%, no weight gain and no hypoglycaemia in the once‐weekly dulaglutide AWARD programme. Issue 1 (3rd November 2015) - Dungan, K. M.; Raz, I.; Skrivanek, Z.; Sealls, W.; Fahrbach, J. L.
Abstract : Aim: To compare the effectiveness of dulaglutide 1.5 and 0.75 mg with active comparators and placebo with regard to a composite endpoint of glycated haemoglobin (HbA1c), weight and hypoglycaemia, using post hoc analyses. Methods: A logistic regression analysis was performed on the intention‐to‐treat population, using data from the last observation carried forward, and the composite endpoint of HbA1c <7.0% (53 mmol/mol), no weight gain (≤0 kg) and no hypoglycaemia (glucose <3.0 mmol/l or severe hypoglycaemia) after 26 weeks for each trial in the AWARD programme separately. Results: At 26 weeks, within each study, 37–58% of patients on dulaglutide 1.5 mg, 27–49% of patients on dulaglutide 0.75 mg, and 9–61% of patients on active comparators achieved the composite endpoint. Significantly more patients reached the composite endpoint with dulaglutide 1.5 mg than with metformin, sitagliptin, exenatide twice daily or insulin glargine: odds ratio (OR) 1.5 [95% confidence interval (CI) 1.0, 2.2; p < 0.05], OR 4.5 (95% CI 3.0, 6.6; p < 0.001), OR 2.6 (95% CI 1.8, 3.7; p < 0.001) and OR 7.4 (95% CI 4.4, 12.6; p < 0.001), respectively, with no difference between dulaglutide 1.5 mg and liraglutide 1.8 mg. In addition, significantly more patients reached the composite endpoint with dulaglutide 0.75 mg than with sitagliptin or insulin glargine: OR 3.3 (95% CI 2.2, 4.8; p < 0.001) and OR 4.5 (95% CI 2.7, 7.8; p < 0.001), respectively. Conclusions: Dulaglutide is an effective treatment option, resulting in a similar or greater proportion of patients reaching the HbA1c target of <7.0% (53 mmol/mol), without weight gain or hypoglycaemia compared with active comparators.